THE REPRESENTATION OF THE EAST IN ENGLISH LITERATURE (17TH TO 20TH CENTURIES) - Ozoda Omonaliyeva Lutfulla qizi; Advisor Erkulova Feruza Melikuziyevna (Web of Journals Publishing, 2025)
In order to better understand how British society's perceptions toward Eastern cultures have changed over time, this article looks at how the East has been portrayed in English literature from the 17th to the 20th centuries. This study analyzes recurrent themes of colonialism, exoticism, and cultural misunderstanding by critically analyzing important literary works. It makes the case that literature was used to support colonial ideas in addition to reflecting current social perspectives. The results show how curiosity and fear interact in a complicated way to shape how the West views the East.
Keywords: 17th and 20th century, colonialism, exoticism, East, English literature, and cultural representation.